2019
DOI: 10.3390/medicina55090522
|View full text |Cite
|
Sign up to set email alerts
|

Opioids Preconditioning Upon Renal Function and Ischemia-Reperfusion Injury: A Narrative Review

Abstract: Kidneys have an important role in regulating water volume, blood pressure, secretion of hormones and acid-base and electrolyte balance. Kidney dysfunction derived from acute injury can, under certain conditions, progress to chronic kidney disease. In the late stages of kidney disease, treatment is limited to replacement therapy: Dialysis and transplantation. After renal transplant, grafts suffer from activation of immune cells and generation of oxidant molecules. Anesthetic preconditioning has emerged as a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 132 publications
(144 reference statements)
0
10
0
Order By: Relevance
“…This phenomenon is induced by a variety of treatments that make neurons more resistant to a subsequent ischemic or hypoxic insult. The most commonly used treatment is the preconditioning with mild ischemia, although the neuroprotective effects of hypoxic, pharmacological, and hyperbaric oxygen preconditioning have also been demonstrated [ 70 , 71 , 72 , 73 ]. It has not been fully revealed how the preconditioned neurons adapt to subsequent ischemic insult, but many scientists agree that it involves multiple protective mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is induced by a variety of treatments that make neurons more resistant to a subsequent ischemic or hypoxic insult. The most commonly used treatment is the preconditioning with mild ischemia, although the neuroprotective effects of hypoxic, pharmacological, and hyperbaric oxygen preconditioning have also been demonstrated [ 70 , 71 , 72 , 73 ]. It has not been fully revealed how the preconditioned neurons adapt to subsequent ischemic insult, but many scientists agree that it involves multiple protective mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine, an imidazole derivative, has a very high selective binding with α2 adrenergic receptor and acts as a α2 adrenergic agonist, with high efficiency and high selectivity. The binding products of dexmedetomidine not only inhibit the sympathetic nervous system, but also can reduce the release of norepinephrine, which helps provide protection to the kidneys ( 24 ). Ammar et al ( 25 ) demonstrated that dexmedetomidine has a protective effect on kidney function in cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The kidneys are responsible for eliminating waste products from the body, controlling blood pressure, and the homeostasis of hormones, water, and solutes [3]. This organ is made up of cortical and medullar zones, containing its functional units, the nephrons.…”
Section: Morphological and Physiological Renal Differences Between Gendersmentioning
confidence: 99%